HISTORISITAS PEMBARUAN HUKUM KELUARGA ISLAM DI SUDAN - Lisnawati, Lisnawati (Al-Maslahah : Jurnal Ilmu Syariah, 2023)
The enforcement of Islamic law includes family law in Sudan has been changing frequently because political upheavals. The formation of the law in Sudan was influenced by the polemic of authority. The efforts to enforce the Islamic Law came from the military coup of 1989, since that the government has been dominated by a combination of military and people from Sudan's National Islamic Front (NIF). The regulatory reform of the Sudanese family is in the form of separate statutes of judges or Manṣūrāt al-Qaḍi al-Quḍat, on marriage, divorce, inheritance, and testaments. Then the Codification of The Personal Status Law for Muslims of 1991 (Family Law), becomes a very important role as a marks the transition of Family Law from the religious field to political field. In subsequent developments, a group of activists united against the concept of qawwama in this legislation, which is thought relegates women into secondary citizens, that’s specifically seen in two aspects: (1) Marriage contract and (2) Obedience in marriage. In 2005, the Comprehensive Peace Agreement stimulated another phase of women's activism and mobilization to reform family law, reformists within the government as well as activists outside of the government have had high hopes for major reform within a ranges of spheres, by introducing initiatives. However, in fact the reformation has not been realized.Keywords: Historicity, Family Law Reform, Sudan